2016
DOI: 10.1177/1934578x1601100532
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Treated Asparagus Extract Attenuates Hydrogen Peroxide-Induced Matrix Metalloproteinase-9 Expression in Murine Skin Fibroblast L929 Cells

Abstract: Enzyme-treated asparagus extract (ETAS) exerts a wide variety of beneficial biological actions including facilitating anti-cortisol stress and neurological antiaging responses. However, the anti-skin aging effects of ETAS remain to be elucidated. Reactive oxygen species (ROS) play pivotal roles in skin aging. Increased ROS levels in fibroblasts in response to ultraviolet irradiation activate c-Jun N-terminal kinase (JNK) and its downstream transcription factor activator protein-1 (AP-1), and the resultant gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…The main enzymes involved in extracellular matrix (ECM) degradation are elastase and matrix metalloproteinases (MMPs). Specific examples of these are gelatinases (MMP-2) and collagenase [2][3]. MMPs activity is accelerated with age and in the presence of reactive oxygen species [2], particularly superoxide anion which is a potent inflammatory mediator [4].…”
mentioning
confidence: 99%
“…The main enzymes involved in extracellular matrix (ECM) degradation are elastase and matrix metalloproteinases (MMPs). Specific examples of these are gelatinases (MMP-2) and collagenase [2][3]. MMPs activity is accelerated with age and in the presence of reactive oxygen species [2], particularly superoxide anion which is a potent inflammatory mediator [4].…”
mentioning
confidence: 99%
“…Cell culture: The murine skin fibroblast cell line L929 (DS Pharma Biomedical, Osaka, Japan) was cultured as previously described [20]. Twenty-four h prior to the initiation of experiments, cells were seeded on culture dishes or multi-well plates at a density of 3.0 × 10 4 cells/cm 2 [20].…”
Section: Preparation Of Etasmentioning
confidence: 99%
“…Cell culture: The murine skin fibroblast cell line L929 (DS Pharma Biomedical, Osaka, Japan) was cultured as previously described [20]. Twenty-four h prior to the initiation of experiments, cells were seeded on culture dishes or multi-well plates at a density of 3.0 × 10 4 cells/cm 2 [20]. To test the effect of H 2 O 2 alone, the cells were treated with or without 1 mM H 2 O 2 (Sigma-Aldrich, St. Louis, MO, USA) and cultured for the desired periods [20].…”
Section: Preparation Of Etasmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme-treated Asparagus Extract (ETAS) is a manufacturing product made from the residual lower parts of asparagus [2]. Some studies have reported about functionalities of ETAS such as anti-inflammatory [3], antioxidative activities [4], the protective effects on early cognitive impairment of senescence-accelerated mouse prone 8 (SAMP8) mice and β-amyloid (Aβ)-induced reduction of PC12 cell (rat pheochromocytoma) viability [5,6].…”
mentioning
confidence: 99%